A semi-continuous algal-bacterial wastewater treatment process coupled with bioethanol production. (15th January 2023) - Papadopoulos, Konstantinos P.; Economou, Christina N.; Stefanidou, Natassa; Moustaka-Gouni, Maria; Genitsaris, Savvas; Aggelis, George; Tekerlekopoulou, Athanasia G.; Vayenas, Dimitris V.
Abstract: Harnessing the biomass energy potential through biofuel production offers new outlets for a circular economy. In this study an integrated system which combine brewery wastewater treatment using algal-bacterial aggregates instead of activated sludge was developed. The use of algal-bacterial aggregates can eliminate the aeration requirements and significantly reduce the high biomass harvesting costs associated with algal monocultures. A sequencing batch reactor (SBR) setup operating with and without biomass recirculation was used to investigate pollutant removal rates, aggregation capacity and microbial community characteristics under a range of hydraulic retention times (HRTs) and solid retention times (SRTs). It was observed that biomass recirculation strategy significantly enhanced aggregation and pollutant removal (i.e., 78.7%, 94.2% and 75.2% for d-COD, TKN, and PO4 3- -P, respectively). The microbial community established was highly diverse consisting of 161 Bacterial Operational Taxonomic Units (B-OTUs) and 16 unicellular Eukaryotic OTUs (E-OTUs). Escalation the optimal conditions (i.e., HRT = 4 d, SRT = 10 d) at pilot-scale resulted in nutrient starvation leading to 38–44% w/w carbohydrate accumulation. The harvested biomass was converted to bioethanol after acid hydrolysis followed by fermentation with Saccharomyces cerevisiae achieving a bioethanol production yield of 0.076 g bioethanol/g biomass. These data suggest that bioethanol production coupled with high-performance wastewater treatment using algal-bacterial aggregates is feasible, albeit less productive concerning bioethanol yields than systems exclusively designed for third and fourth-generation biofuel production. Highlights: Semi-continuous wastewater treatment using photosynthetic aggregates studied. Optimal operating conditions (HRT = 4 d, SRT = 10 d) escalated in a 30 L open pond. Biomass recirculation achieved over 75% pollutant removal and up to 94% settling efficiencies. Recovered carbohydrate-enriched aggregates converted to bioethanol.